The Influence of National Competition Policy on the International Competitiveness of Nations A Contribution to the Debate on International Competition Rules - Mitschke, Andreas; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2008)
Two fields of economic research in competition policy have gained in importance in times of economic globalization. Firstly, globalization has resurrected the debate whether there is a need for international competition rules against private anticompetitive practices and how these rules could be implemented in the best way. Secondly, the concept of the international competitiveness of nations has become a significant issue for all open economies. The discussion of both themes directs the attention to a specific interface of these two issues. The implementation of international competition rules would limit or even eliminate national competition policy. The matter in question is to what extent national competition policy has to be regarded as a factor of international competitiveness so that national antitrust policy should be given priority over international antitrust rules.
About the Necessity of International Competition Rules -- The International Competitiveness of Nations -- National Competition Policy and International Competitiveness -- Concluding Remarks.
Keywords: International economics; Economic policy; Economic growth; Economics; Economic Policy; International Economics; Economic Growth; Electronic books